Implementation of Character Values Through Physical Education, Sports, and Health Education: A Thematic Analysis Approach Using ATLAS.ti - Bahri, Samsul; Yuliarto, Hari (Champions: Education Journal of Sport, Health, and Recreation, 2025)
Character is the traits or qualities that shape a person's personality, including behaviour, values, and morality, which are reflected in the actions and decisions made in everyday life. The purpose of this study is to determine the implementation of character values in physical education, sports, and health subjects. Qualitative research methods were used to obtain and explore information about the implementation of character education in physical education, sports, and health subjects using data collection techniques such as observation, interviews, and documentation. The data was analysed using ATLAS. The process involved several stages: project analysis, data processing, familiarisation with the data, coding, solidification and integration of the coding system, categorisation of codes, categorisation of categories, co-occurrence menu, and thematic visualisation. The research results indicate that PJOK teachers and school principals consistently instil good habits in students during the learning process, both before and after lessons begin. This study has implications for the development of PJOK learning that focuses not only on physical and cognitive aspects, but also on character building in students.